Navigating The Landscape Of Innovation & Entrepreneurship In Pakistan: A Review - Hanif, Muhammad Iftikhar; Butt, Asif Maqsood; Asif, Omaima (Journal of Rawalpindi Medical College, 2025)
This article’s abstract explores the concepts of innovation and entrepreneurship and how they work together to promote economic progress. Despite its challenges, Pakistan may prosper in these fields thanks to its large and growing market, skilled labour force, and supportive political environment. However, for innovation and entrepreneurship to live up to their potential, several problems need to be resolved, including bureaucracy and corruption, poor intellectual property protection, inadequate research and development, and limited access to capital. In the medical device industry, innovation and entrepreneurship may drive progress as new technologies and opportunities for expansion and improvement can be developed. Getting finance, negotiating legal and regulatory environments, managing new trends and technologies, The potential for coordinated effort and organisation, and laying the basis for a flourishing enterprising biological system in Pakistan are points shrouded in this article. The article makes various significant proposals for Pakistani entrepreneurs who must work on their odds of coming out on top, including making a strong marketable strategy, finding finance sources, interfacing with others and cooperating, using innovation, and being versatile. Pakistan can lead the way nearby for advancement and business, setting the way for monetary development and improvement, with continuous endeavours and participation. Keywords: Innovation, Entrepreneurship, Economic growth, venture, Value, Workforce, Research and development, Medical device, Networking, Technology, Adaptability, Success.